THE IMPLEMENTATION OF QUESTION-ANSWER RELATIONSHIPS (QAR) STRATEGY TO IMPROVE READING COMPREHENSION OF STUDENTS AT SMA NEGERI 5 LUBUK LINGGAU - Sagita (Lingustic, Literature and English Education, 2025)
This study aims to investigate the effectiveness of the Question-Answer Relationship (QAR) strategy in improving the reading comprehension of eleventh-grade students at SMA Negeri 5 Lubuklinggau. The background of this research stems from students' low comprehension skills, particularly in understanding the structure and meaning of explanation texts. The study employed a quantitative method using a pre-experimental design with one group pre-test and post-test. The sample consisted of 33 students from class XI-F4, selected through cluster random sampling. The research instrument was a multiple-choice reading comprehension test focused on explanation texts. Data were analysed using the Chi-Square method for normality testing and a paired t-test for hypothesis testing. The results revealed that the students’ average score improved from 63.78 in the pre-test to 75.06 in the post-test. The paired sample t-test showed a significant difference (tcount = 6.05 > ttable = 1.697), indicating that the QAR strategy had a positive effect on students’ reading comprehension. The findings suggest that QAR enhances students’ ability to comprehend texts by training them to classify and answer different types of questions. This strategy also promotes active reading, critical thinking, and student engagement. Therefore, the QAR strategy is recommended for use in teaching reading, particularly explanation texts, at the senior high school level. Future research is encouraged to apply the QAR strategy to different text genres or in combination with digital media to further explore its broader applicability in diverse learning contexts.